Meta-analysis on sex differences in mortality and neurodevelopment in congenital heart defects - Alyssa K. Crain; Zhia N. Lim; Chloe J. Sarfatis; Magela Arias; Travis Holder; Alvaro G. Moreira; Antonio F. Corno; Tina O. Findley (Scientific Reports)
Abstract Given the increasing survival rates among congenital heart disease (CHD) patients and the growing emphasis on their quality of life, there is a need to comprehensively assess the impact of surgical interventions on neurodevelopmental outcomes. With increasing awareness in sex-related disparities in CHD, there is a need to explore potential differences in surgical mortality and neurodevelopmental outcomes between male and female patients. In this systematic review, we adhered to PRISMA guidelines and PROSPERO registration (#CRD42021225610). Articles published from 2015 to 2021 were searched using MeSH descriptors in three major databases (MEDLINE Ovid, Elsevier Embase, and Cochrane Library). Study selection criteria focused on pediatric (< 18 years of age) CHD patients undergoing primary cardiac surgery. A total of 163 articles that met inclusion criteria were reviewed. The definition and assessment of neurodevelopmental impairment, data extraction, risk of bias assessment, and statistical analysis methods were adhered by blinded reviewers. Previous studies have reported higher rates of early childhood mortality in female patients and higher rates of neurodevelopmental impairment in male patients with CHD requiring surgery. Our meta-analysis suggests that these differences may no longer be valid in contemporary surgical cohorts. However, it is unclear if sex-related risk factors have truly been mitigated with current surgical and medical approaches Our meta-analysis does underscore the need for further research considering sex as a variable and for additional investigative efforts in long term neurodevelopmental outcomes.